Understanding the effect of lipid formulation loading and ethanol as a diluent on solidification of pitavastatin super-saturable SNEDDS using factorial design approach - Ilham Kuncahyo; Syaiful Choiri; Achmad Fudholi; Abdul Rohman; Ronny Martien (Wolters Kluwer Medknow Publications, 2019)
Solidification of a preconcentrate lipid formulation namely self-nano emulsifying drug delivery system (SNEDDS) is required to achieve feasibility, flexibility, and a new concept of "dry nano-emulsion". The purpose of this study was to assess the effect of SNEDDS loading and ethanol as a diluent on the solidification of pitavastatin supersaturable SNEDDS (S-SNEDDS). A 22 full factorial design approach with a center point addition as a curvature was implemented to determine the effect of S-SNEDDS loading and ethanol on the physical characteristics, namely flowability, compactibility, and drug release behavior. Vibrational spectra, thermal behavior, and morphology of solid S-SNEDDS formulation were also evaluated. The results indicated that there was no interaction between S-SNEDDS and carrier, based on vibrational spectra. However, thermal behaviors (enthalpy and weight loss) were depending on SNEDDS loading. Thereafter, the ethanol as a diluent of preconcentrated formulation had no effect on the morphology of carrier structure. However, the S-SNEDDS loading altered the structure of carrier owing to either solubilization or abrasion processes. The statistical model suggested that ethanol as diluent reduced the flowability, compactibility, and drug releases. Meanwhile, the liquid SNEDDS loading affected the reducing of flowability and compactibility. Finally, solidification without diluent and 20% lipid formulation load was recommended. In addition, it was very useful because of ease on handling, flexibility for further formulation, and desired characteristics of final solid dosage form.